Prophylactic Ozone Administration Reduces Intestinal Mucosa Injury Induced by Intestinal Ischemia-Reperfusion in the Rat - Ozkan Onal; Fahri Yetisir; A. Ebru Salman Sarer; N. Dilara Zeybek; C. Oztug Onal; Banu Yurekli; H. Tugrul Celik; Ayse Sirma; Mehmet Kılıc (Mediators of Inflammation)
Objectives. Intestinal ischemia-reperfusion injury is associated with mucosal damage and has a high rate of mortality. Various beneficial effects of ozone have been shown. The aim of the present study was to show the effects of ozone in ischemia reperfusion model in intestine. Material and Method. Twenty eight Wistar rats were randomized into four groups with seven rats in each group. Control group was administered serum physiologic (SF) intraperitoneally (ip) for five days. Ozone group was administered 1 mg/kg ozone ip for five days. Ischemia Reperfusion (IR) group underwent superior mesenteric artery occlusion for one hour and then reperfusion for two hours. Ozone + IR group was administered 1 mg/kg ozone ip for five days and at sixth day IR model was applied. Rats were anesthetized with ketamine∖xyzlazine and their intracardiac blood was drawn completely and they were sacrificed. Intestinal tissue samples were examined under light microscope. Levels of superoxide dismutase (SOD), catalase (CAT), glutathioneperoxidase (GSH-Px), malondyaldehide (MDA), and protein carbonyl (PCO) were analyzed in tissue samples. Total oxidant status (TOS), and total antioxidant capacity (TAC) were analyzed in blood samples. Data were evaluated statistically by Kruskal Wallis test. Results. In the ozone administered group, degree of intestinal injury was not different from the control group. IR caused an increase in intestinal injury score. The intestinal epithelium maintained its integrity and decrease in intestinal injury score was detected in Ozone + IR group. SOD, GSH-Px, and CAT values were high in ozone group and low in IR. TOS parameter was highest in the IR group and the TAC parameter was highest in the ozone group and lowest in the IR group. Conclusion. In the present study, IR model caused an increase in intestinal injury.In the present study, ozone administration had an effect improving IR associated tissue injury. In the present study, ozone therapy prevented intestine from ischemia reperfusion injury. It is thought that the therapeutic effect of ozone is associated with increase in antioxidant enzymes and protection of cells from oxidation and inflammation.